Transposable Elements in Pluripotent Stem Cells and Human Disease - Ma, Gang; Babarinde, Isaac A.; Zhou, Xuemeng; Hutchins, Andrew P. (Frontiers in Genetics, 2022)
Transposable elements (TEs) are mobile genetic elements that can randomly integrate into other genomic sites. They have successfully replicated and now occupy around 40% of the total DNA sequence in humans. TEs in the genome have a complex relationship with the host cell, being both potentially deleterious and advantageous at the same time. Only a tiny minority of TEs are still capable of transposition, yet their fossilized sequence fragments are thought to be involved in various molecular processes, such as gene transcriptional activity, RNA stability and subcellular localization, and chromosomal architecture. TEs have also been implicated in biological processes, although it is often hard to reveal cause from correlation due to formidable technical issues in analyzing TEs. In this review, we compare and contrast two views of TE activity: one in the pluripotent state, where TEs are broadly beneficial, or at least mechanistically useful, and a second state in human disease, where TEs are uniformly considered harmful.